Precious cargo : a novel of suspense - Ford, Clyde W. (Vanguard Press, 2008)
Still reeling from the untimely death of his wife, Charlie Noble begins to warm to the idea of a second chance at true love with new girlfriend Kate Sullivan. These plans are quickly docked when boating friends Marvin and Angela Baynes come to him with a horrifying discovery<U+2014>the body of an unidentified young woman impaled on the flukes of their boat anchor. The Bayneses themselves lost a child years ago. No stranger to loss, Charlie finds it impossible not to help them<U+2014>even though it could mean putting his new romance in jeopardy.